2015
DOI: 10.1007/s13204-015-0487-6
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of zinc oxide nanoparticles using Ruta graveolens (L.) and their antibacterial and antioxidant activities

Abstract: In the present investigation, green synthesis of zinc oxide nanoparticles were successfully synthesized by biological method using aqueous stem extract of Ruta graveolens act as reducing agent. Formation of ZnO nanoparticles were characterized by powder X-ray diffraction (PXRD), UV-visible spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) techniques. Zinc oxide nanoparticles were subjected to biological properties such as antibacterial and antioxidant studies. The PXRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(43 citation statements)
references
References 35 publications
6
36
1
Order By: Relevance
“…The spectra of the non-annealed nano powder displayed an amorphous signature. The annealed nano powder showed peaks that can be indexed to the hexagonal wurtzite structure ZnO, which coincide with the standard JCPDS card (202) plane [37]. The strong sharp diffraction peak indicate that ZnO nanoparticles annealed at 500°C are well crystallized [6,31].…”
Section: Electrochemistrysupporting
confidence: 63%
See 1 more Smart Citation
“…The spectra of the non-annealed nano powder displayed an amorphous signature. The annealed nano powder showed peaks that can be indexed to the hexagonal wurtzite structure ZnO, which coincide with the standard JCPDS card (202) plane [37]. The strong sharp diffraction peak indicate that ZnO nanoparticles annealed at 500°C are well crystallized [6,31].…”
Section: Electrochemistrysupporting
confidence: 63%
“…Lastly the peak at 300°C is due to the formation of Zinc Oxide nanoparticles and decomposition of organic matter [35,36] High Resolution Transmission Electron Microscope (HRTEM) Figure 3 reports a typical High-Resolution Transmission Electron Microscope (HRTEM), Energy Dispersive X-Ray (EDX) as well as Selected Area Electron Diffraction (SAED) of ZnO nanoparticles annealed at 500°C in air. Figure 3a shows that the particles were highly agglomerated quasi-spherical in shape [37]. The average diameter of the nanoparticles was found to be of the order of (f particles ) ≈ 28.09 ± 5 nm.…”
Section: Thermogravimetric Analysis Tga/differential Scanning Calorimmentioning
confidence: 97%
“…Antibacterial activity of synthesized formamides was screened by agar well di usion method [51,52] against pathogenic bacterial strains such as G ve bacteria Escherichia coli (NCIM-5051) and G +ve bacteria Staphylococcus aureus (NCIM-5022). The nutrient medium was prepared by dissolving 37.0 g of nutrient nutrient agar medium was poured into petri-dishes and allowed to solidify.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…On the other hand, in a recent study, they have observed DPPH scavenging activity of synthesized silver nanoparticles extracted from leaf samples and they have found highest activity as 4.30 µg/ml [34]. Similarly, in Lingaraju et al [35], synthesized ZnO nanoparticles showed good scavenging activity with inhibitory concentration (IC 50 ) value of 9.34 mg/ml. In a recent study, they have also got the similar results [36].…”
Section: Discussionmentioning
confidence: 89%